Hubungan Karakteristik Individu, Kemampuan, dan Motivasi dengan Kinerja Perawat di Ruang Rawat Inap Rumah Sakit Umum Daerah Syekh Yusuf Gowa - Setyowati1, Rika; Rachmawati, Emma; Rahayu, Sri (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2024)
The achievement performance indicator is a variable to measure and assess the quality of service that has an impact on health services. The purpose of this study was to determine the relationship between nurse performance in the Inpatient Room of the Syekh Yusuf Gowa Regional General Hospital in 2022. This quantitative research design is Cross Sectional. Data were collected through questionnaires distributed in December 2022 - January 2023. The sample in the study amounted to 115 nurses in the inpatient room of the Syekh Yusuf Gowa Regional General Hospital and proportional random sampling technique. The results showed that there was a relationship between the performance of nurses in the inpatient room of the Regional General Hospital of Syekh Yusuf Gowa with age (p value = 0.000), education (p value = 0.999), legal and cultural ethical professional abilities (p value = 0. 018), (professional development ability (p value = 0.008), physiological motivation (p value = 0.000), security motivation (p value = 0.001), affiliation motivation (p value = 0.010), reward motivation (p value = 0.005), and self-actualization motivation (p value value = 0.012). The variable that has a significant effect on the performance of nurses in the inpatient room of the Syekh Yusuf Gowa Regional General Hospital is motivation as safe, the recommendation of this study is that hospital management can make improvements to the welfare and guarantee of nurses in increasing the motivation of a sense of security.